Insights Into SND1 Oncogene Promoter Regulation - Ochoa, Begoña; Chico, Yolanda; Martínez, María José (Frontiers in Oncology, 2018)
The staphylococcal nuclease and Tudor domain containing 1 gene (SND1), also known as Tudor-SN, TSN or p100) encodes an evolutionarily conserved protein with invariant domain composition. SND1 contains four repeated staphylococcal nuclease domains and a single Tudor domain, which confer it endonuclease activity and extraordinary capacity for interacting with nucleic acids, individual proteins and protein complexes. Originally described as a transcriptional coactivator, SND1 plays fundamental roles in the regulation of gene expression, including RNA splicing, interference, stability and editing, as well as in the regulation of protein and lipid homeostasis. Recently, SND1 has gained attention as a potential disease biomarker due to its positive correlation with cancer progression and metastatic spread. Such functional diversity of SND1 marks this gene as interesting for further analysis in relation with the multiple levels of regulation of SND1 protein production. In this review, we summarize the SND1 genomic region and promoter architecture, the set of transcription factors that can bind the proximal promoter, and the evidence supporting transactivation of SND1 promoter by a number of signal transduction pathways operating in different cell types and conditions. Unraveling the mechanisms responsible for SND1 promoter regulation is of utmost interest to decipher the SND1 contribution in the realm of both normal and abnormal physiology.